2006
DOI: 10.1021/ed083p1499
|View full text |Cite
|
Sign up to set email alerts
|

Dulong and Petit's Law: We Should Not Ignore Its Importance

Abstract: Dulong and Petit's law played an important role in the development of the periodic table as Mendeleyeff used this method in 1870 to correct the atomic weights of indium, cerium, and uranium that were wrong in the table of 1869. The discontinuous variation of molar heat capacity of a solid with change in temperature can be due to a phase change, order–disorder phenomena, or magnetic transitions. Two student exercises are described: the determination of the specific heat of a metal and hence its atomic weight (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 4 publications
1
15
0
Order By: Relevance
“…The carrier concentration ( n H ) and mobility ( μ H ) were performed by the Hall effect measurement system (HMS-3000, ECOPIA) on the sanded samples (thickness about 500 μm) in constant magnetic fields of up to ±0.525 T. The thermal diffusivity ( D ) of our pellet samples (diameter of ∼12.7 mm and thickness of ∼1.8 mm) was obtained by using a laser flash method (XFA 1000, Linseis). κ tot could be obtained by using κ tot = DC p d where d is the density of the sintered samples; all the specific heat capacity ( C p ) were used with the theoretical value ( C p ≈ 0.318 Jg –1 K –1 , which is calculated by the Dulong–Petit formula , ).…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The carrier concentration ( n H ) and mobility ( μ H ) were performed by the Hall effect measurement system (HMS-3000, ECOPIA) on the sanded samples (thickness about 500 μm) in constant magnetic fields of up to ±0.525 T. The thermal diffusivity ( D ) of our pellet samples (diameter of ∼12.7 mm and thickness of ∼1.8 mm) was obtained by using a laser flash method (XFA 1000, Linseis). κ tot could be obtained by using κ tot = DC p d where d is the density of the sintered samples; all the specific heat capacity ( C p ) were used with the theoretical value ( C p ≈ 0.318 Jg –1 K –1 , which is calculated by the Dulong–Petit formula , ).…”
Section: Experimental Sectionmentioning
confidence: 99%
“…A.T. Petit and P.L. Dulong measured how fast solid bodies cooled down in low pressure air and found that the specific heat capacities of the bodies were inversely proportional to the atomic weights of the bodies' chemical elements [1,24]. Therefore, the Dulong-Petit law states that the product of the molar mass, M , with the specific heat, C V , of mono-atomic solid bodies, i.e., the molar specific heat,…”
Section: B Molar Specific Heatmentioning
confidence: 99%
“…The Dulong-Petit law was important not only in physics, but also in chemistry, where it helped Dmitry Mendeleev to discover the periodic table of chemical elements [24]. Mendeleev used the Dulong-Petit law to correct wrong atomic weights of three elements (cesium, uranium and indium) by making new measurements of their specific heats.…”
Section: B Molar Specific Heatmentioning
confidence: 99%
“…Interestingly, a similar behavior has been observed for systems containing light atoms that are strongly bonded to each other, causing some vibrational modes to be unpopulated even at 300 K due to their high vibrational frequencies. 54 This indicates the presence of complex vibrational behavior in this material with strong anharmonicity, 55 which should be studied further by other techniques such as inelastic neutron scattering. In general , beyond structural phase transitions, thermochromism can also be induced by subtle changes to the bond distances and angles in metal halides such as in the case of the related iodobismuthates featuring isolated…”
Section: Resultsmentioning
confidence: 92%